2001
DOI: 10.1093/jxb/52.359.1179
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic stress leads to hydrogen peroxide formation in plant cells

Abstract: Hydrogen peroxide (H2O2) was detected cytochemically in plant tissues during anoxia and re-oxygenation by transmission electron microscopy using its reaction with cerium chloride to produce electron dense precipitates of cerium perhydroxides. Anoxia-tolerant yellow flag iris (Iris pseudacorus) and rice (Oryza sativa), and anoxia-intolerant wheat (Triticum aestivum) and garden iris (Iris germanica) were used in the experiments. In all plants tested, anoxia and re-oxygenation increased H2O2 in plasma membranes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 27 publications
4
85
0
1
Order By: Relevance
“…Water-logging induced increase in the activity of diphenylene iodonium chloride-sensitive NADPH oxidase dependent superoxide production as well as increase in the expression of NADPH oxidase has been reported in pigeon pea (Kumutha et al 2009 andSairam et al 2009b). Blokhina et al (2001) reported H 2 O 2 formation during anoxia as evidenced by electron dense insoluble precipitate of cerium perhydroxide, visualized through electron microscope. Greater ROS production in tolerant genotypes V. luteola and T 44 under water-logging could also have a role in signaling anaerobiosis tolerance mechanism, as H 2 O 2 signaling has been reported in the induction of ADH gene (Fukao and Bailey-Serres 2004) and SOD and APX (Agarwal et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-logging induced increase in the activity of diphenylene iodonium chloride-sensitive NADPH oxidase dependent superoxide production as well as increase in the expression of NADPH oxidase has been reported in pigeon pea (Kumutha et al 2009 andSairam et al 2009b). Blokhina et al (2001) reported H 2 O 2 formation during anoxia as evidenced by electron dense insoluble precipitate of cerium perhydroxide, visualized through electron microscope. Greater ROS production in tolerant genotypes V. luteola and T 44 under water-logging could also have a role in signaling anaerobiosis tolerance mechanism, as H 2 O 2 signaling has been reported in the induction of ADH gene (Fukao and Bailey-Serres 2004) and SOD and APX (Agarwal et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide accumulation under hypoxic conditions has been shown in the roots and leaves of Hordeum vulgare (Kalashnikov Ju et al 1994) and in wheat roots (Biemelt et al 2000). The presence of H 2 O 2 in the apoplast and in association with the plasma membrane has been visualized by transmission electron microscopy under hypoxic conditions in four plant species (Blokhina et al 2001). Recently Kumutha et al (2009) and Sairam et al (2009b) have shown that hypoxia induced ROS in pigeon pea roots are due to induction of membrane linked NADPH oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…4A; Nishizawa et al, 2006). The production of H 2 O 2 , therefore, may be the trigger for HsfA2 and HSP expression following either heat or anoxic treatment (Blokhina et al, 2001;Volkov et al, 2006). H 2 O 2 is quickly produced after the onset of both treatments ( Fig.…”
Section: Heat Pretreatment Dampens the Anaerobic Responsementioning
confidence: 99%
“…Blokhina e colaboradores (Blokhina et al 2001) demostraram que em resposta à anóxia, as plantas de trigo apresentam um acúmulo acentuado de H 2 O 2 no apoplasto de meristemas da raiz. Níveis baixos de oxigênio aumentam a concentração de H 2 O 2 fazendo com que dois genes, um chamado Rop e outro RopGAP4, tenham suas expressões controladas.…”
Section: Sinalização Metabólica E Hormonal Durante O Alagamentounclassified